Properties of novel diallyl phthalate resin modified with sulfur‐containing allyl ester compounds. Issue 4 (12th August 2013) - Ohtsuka, Keiko; Kimura, Hajime; Iwai, Toshiyuki; Matsumoto, Akihiro
Abstract Sulfur‐containing allyl ester, which reacts with diallyl phthalate (DAP) resin to have allyl groups, was synthesized by the reaction of allyl phthalic acid with bisphenol having sulfur atoms. The sulfur‐containing allyl ester compound was blended with DAP resin to improve the adhesive properties to copper. By modification with sulfur‐containing allyl ester compound, the T‐peel adhesive strength and the lap shear adhesive strength to copper was improved. In particular, the adhesive strength was greatly improved when the resin was modified with the allyl ester compound having a disulfide bond (−S−S−) (DADS). It is concluded that this result is due to the improvement of the interfacial adhesive strength because the sulfur atom was found to be located in the surface of the copper by Fourier transform infrared (FTIR) analysis. The glass transition temperature (Tg) and the thermal decomposition temperature (Td) of the cured DAP resin modified with DADS slightly decreased with increasing concentration of DADS. The lowering of Tg is because the crosslinking density of the DAP resin modified with DADS is smaller than that of DAP resin. Moreover, from thermogravimetric analysis, the lowering of Td of the DAP resin modified with DADS is because DADS is likely to pyrolyze. © 2013 Society of Chemical Industry